Differences Between South American H Haplome Diploids and I Haplome Diploids from the Perspective of the 5S rDNA Gene in the Genus Hordeum - B.R. Baum; D.J. Johnson (Czech Journal of Genetics and Plant Breeding, 2004)
Twelve South American diploid Hordeum species belonging to the H genome and three diploid species belonging to the I genome (including cultivated barley) were investigated for their 5S rDNA sequence diversity. The 374 sequenced clones were assigned to classes called "unit classes" which were further assigned to haplomes. Two unit classes were found to be present in each haplome. These were labelled to reflect the haplomes, viz. the long H1 and short I1 unit classes for the I haplome diploids, and the long H2 and long Y2 unit classes for the South American H genome diploids. The aligned sequences were subjected to a series of Maximum Likelihood analyses and various tests, including molecular clock, which are presented and discussed. The divergences among the unit classes suggest that the genus Hordeum might be of paleopolyploid origin.